Possibilities of screening for a high-risk axial skeletal lesion in psoriatic arthritis - E. E. Gubar; E. Yu. Loginova; Yu. L. Korsakova; S. I. Glukhova; T. V. Korotaeva (Современная ревматология, 2020)
Objective: to determine a set of signs that are prognostically significant for identifying a high-risk axial skeletal lesion in early psoriatic arthritis (ePsA).Patients and methods. Examinations were made in 95 patients (47 men and 48 women) with peripheral arthritis lasting for ≤2 years, who met the 2006 Classification Criteria for Psoriatic Arthritis (CASPAR). The clinical characteristics of the patients were presented in our previously published work. In all the patients, a standard examination was made and the signs of inflammatory back pain (IBP) were identified according to the Assessment of SpondyloArthritis International Society (ASAS) criteria, the presence of human leukocyte antigen B27 (HLA-B27) was determined, and pelvic bone X-ray was done; regardless of whether they had IBP, 79 patients underwent magnetic resonance imaging (MRI) of the sacroiliac joints using a low-field Signa Ovation 0.35 T. Sacroiliitis (SI) diagnosed based on radiography (rSI) was considered reliable if there were bilateral changes corresponding to at least Stage II or unilateral changes corresponding to at least Stage III according to the Kellgren system. SI diagnosed based on MRI (MRI-SI) was regarded as active when osteitis was detected in the STIR mode in the bones adjacent to the joint on at least two slices or in the presence of two signals in a slice. X-ray and MRI results were assessed by an independent radiologist. The extent of a skin lesion was determined from the body surface area (BSA): the extent was regarded insignificant, moderate, and significant with involvements of <3%, 3–10%, and >10%, respectively.The patients were divided into two groups. Group 1 included 65 (68.4%) patients with the manifestations of axial PsA (axPSA): IBP, and/or rSI, and/or MRI-SI; Group 2 consisted of 30 (31.6%) patients without axial manifestations, only with peripheral PsA (pPsA). Multivariate stepwise discriminant analysis was used to identify a group of signs that were most characteristic of axPsA.Results and discussion. Comparative analysis of the two groups showed that there were more males among patients with axPsA than among those with pPsA (39 (60%) and 8 (26.7%), respectively) (p=0.003). HLA-B27 positivity was also more often detected in patients with axPSA than in those with pPsA (30 (46.6%) and 7 (23.3%) patients, respectively) (p=0.02). In the axPSA group, there were significantly more individuals with moderate and high DAS, high CRP levels, and a more severe skin lesion (BSA >3%).The investigators obtained the following discriminant classification rule associated with axPSA: 1.566 (if CRP is >5 mg/L) + 0.957 (if HLA-B27 is positive) + 0.986 (if BSA is >3%) + 1.845 (if DAS is moderate or high) + 0.6 (if the sex is male) >3.751 (p=0.0025). The sensitivity and specificity of the model were 68% and 73%, respectively.Conclusion. The combination of signs, such as male sex, HLA-B27 positivity, high or moderate DAS, CRP >5 mg/L, the extent of skin lesions according to BSA >3%, is prognostically significant for identifying high-risk axial skeletal lesion in ePSA. The proposed mathematical model can be used to screen patients for the early diagnosis of an axial lesion in ePSA.